Penerapan Sistem Pengendalian Intern Pemerintah (Spip) Dan Standar Operasional Prosedur (Sop) Terhadap Pencegahan Fraud Pada Pengelolaan Dana Desa (Studi Pada Desa Di Kecamatan Wanggarasi Kabupaten Pohuwato) - Wahyuni, Wahyuni; Mattoasi, Mattoasi; Monoarfa, Valentina (STIE Amkop Makassar, 2024)
Study This aim Forknow influence application system government internal controls and standards operational procedure to prevention fraud in village fund management in the District Wanggarasi, Regency Pohuwato. Method used in study This is method quantitative, with spread questionnaire to 35 respondents. Research results show in a way Partial variable system government internal control and variables standard operational procedure to prevention fraud in village fund management with magnitude influence 87%, meanwhile the rest that is of 13% is influence other existing variables in structure theory But No tested in study This like Professional Audit, Competency Human Resources and Good Corporate Governance as well variable other existing ones relationship with prevention village fund management fraud.